THE IMPLEMENTATION OF THE PROBLEM-BASED LEARNING (PBL) MODEL TO IMPROVE STUDENTS’ LEARNING OUTCOMES ON THE CONTINENT TOPIC IN GRADE VI OF SD NEGERI 007 BANGUN PURBA - Kusuma, Mutri; Efendi, Rinja (Perspektif Ilmu Pendidikan, 2026)
This study aims to improve students’ learning outcomes on the topic of Continents through the implementation of the Problem-Based Learning (PBL) model in Grade VI of SD Negeri 007 Bangun Purba. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects were 28 students. Data were collected using learning outcome tests (pretest and posttest), teacher and student activity observation sheets, and documentation. Data analysis was carried out both quantitatively and qualitatively, with a minimum mastery criterion (KKM) of 75. The results showed a significant improvement in students’ learning outcomes after the implementation of the PBL model. The average score increased from 65 with 53.6% mastery in the pre-cycle, to 75 with 71.4% mastery in the first cycle, and reached 83 with 89.3% mastery in the second cycle. In addition to cognitive improvement, students demonstrated better learning engagement, such as increased participation in group discussions, confidence in expressing opinions, and collaboration in solving problems. Therefore, the implementation of the Problem-Based Learning (PBL) model proved effective in improving students’ learning outcomes and social skills in social studies at the elementary school level.